Investigation of the Effects of Fosfomycin in Kidney Damage Caused by CLP-Induced Sepsis - Ilknur Esen Yildiz; Tolga Mercantepe; Ilkay Bahceci; Medeni Arpa; Sule Batcik; Yasin Yildiz; Levent Tumkaya (Life)
Sepsis, a life-threatening condition characterized by dysregulated host responses to infection, often leads to multi-organ dysfunction, including kidney injury. Kidney damage in sepsis can have severe consequences and is associated with high mortality rates. This study aimed to investigate the potential therapeutic effects of fosfomycin (FOS), a broad-spectrum antibiotic with immunomodulatory properties, on kidney damage induced by cecal ligation and puncture (CLP)-induced sepsis in a rodent model. In total, 24 rats were randomly divided into three groups. Group 1 (n = 8), the healthy control group (C), received a single dose of 0.9% NaCl (saline) solution via an intraperitoneal (i.p.) route. To group 2 (n = 8), the CLP group, CLP-induced sepsis was applied without medication, and a single dose of 0.9% NaCl (saline) solution was applied i.p. before induction. To group 3 (n = 8), the CLP + FOS (500 mg/kg) group, a single dose of 500 mg/kg FOS was administered i.p. before sepsis induction. The effects of fosfomycin on kidney function, histopathological changes, inflammatory markers, oxidative stress, and apoptosis were assessed. In the fosfomycin-treated group, the histological analysis results demonstrated reduction in kidney tissue damage and inflammation. Additionally, fosfomycin attenuated the upregulation of pro-inflammatory cytokines and reduced oxidative stress markers in kidney tissue. Furthermore, fosfomycin treatment was associated with a decrease in apoptotic cell death in the kidney. These findings suggest that fosfomycin may have a protective effect on kidney damage caused by CLP-induced sepsis. The potential mechanisms underlying this protection include the modulation of inflammation, reduction of oxidative stress, and inhibition of apoptosis.